ANALISA STRATEGI SISTEM INFORMASI MENGGUNAKAN PENDEKATAN METODESWOT DI BANDUNGINSIGHT - Nova Indrayana Yusman (Jurnal Accounting Information System (AIMS), 2019)
Bandung Insight is a company that has just been established in mid 2018, and has just begun in the field of information systems. For a new company, and of course there are still many shortcomings in various fields. And according to the observations of the author,  the system that is used today is just working alternately, because it has not found the right information system that will be used in the future.In this system, data retrieval uses survey methods in collecting and processing information data to contain an overview of the situation in the object of the studies. As for the design of the information system, the author tries to use the SWOT analysis approach. Why? Because the reasoning of this system will be useful if its implementation is in accordance with the goals, vision and mission of the company by implementing information strategies and business strategies.